IMPLEMENTASI AMALAN DZIKIR ASMAUL HUSNA DALAM PEMBENTUKAN KONTROL DIRI SISWA DI SMAN 4 PASURUAN - Imam Muttaqin; Miftakhul Munir; Dwi Novianti Ramadhani (Jurnal Pendidikan Islam, 2025)
With Asmaul Husna dhikr, students are expected to become calmer, less prone to anger, and more positive and optimistic each day. The aim of this study is to understand how the implementation of Asmaul Husna dhikr at SMAN 4 Pasuruan contributes to the development of students' self- control, as well as to identify factors that support or hinder the implementation of Asmaul Husna dhikr in enhancing students' spiritual awareness and self-control. This research uses a qualitative approach with a case study design to understand the implementation of Asmaul Husna dhikr in shaping students' self- control attitudes at SMAN 4 Pasuruan. It involves various research methods such as interviews, observations, and document analysis. The case study focuses on a specific location to explore the context, process, and outcomes of the dhikr program in depth. Data is collected through direct observation techniques, in-depth interviews, and documentation, while data validity is ensured through triangulation, which involves comparing data from various sources and different data collection techniques. The results of this study show that the implementation of Asmaul Husna dhikr at SMAN 4 Pasuruan is structured through daily and annual programs, where students perform dhikr every morning before lessons and during Islamic holidays. The purpose of this implementation is to develop students' self-control and enhance their calmness, emotional regulation, discipline, ethics, and empathy. The results indicate an improvement in self-control, calmness, emotional regulation, discipline, as well as students' ethics and empathy, contributing positively to a conducive school environment. Supporting factors for the program's success include internal support from the principal and students, as well as a conducive environment